Developing Android-Based Educational Games to Improve Students' Literacy in Whole Number - Susanti, Ely; Aisyah, Nyimas; Suryani , Eka (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
(During the learning process, the use of media and teaching materials, as well as non-routine questions, can help students improve their understanding and literacy in mathematics. One of them is game-based media designed or created to stimulate thinking skills to improve concentration and problem-solving, with attractive features such as audio, text, images, and moving animations, utilizing only links and tools on each individual's Android phone. This is also in line with the use of technology-based media in learning as formulated by the Ministry of Education and Culture through the Merdeka Curriculum. This research aims to produce valid and practical educational math game materials in the form of an Android-based game and to describe students' responses after using the game. The subjects of this research are 33 seventh-grade students from SMP SRIJAYA Palembang. The research method used is Development Research, with the model applied in the learning process being the Plomp model, which consists of 2 stages: preliminary research and prototyping. The data collection techniques are questionnaires, observations, interviews, and tests. The questionnaire is used to assess the validity and practicality of the teaching materials. Observation is used to measure learning effectiveness, while tests are used to measure students' mathematical literacy. The data analysis technique used in this research is descriptive, both quantitative descriptive and qualitative descriptive. Based on the results of the data analysis, it was found that the developed Android-based game is categorized as valid when viewed from the aspects of content, construct, language, and ICT. In addition, the Android-based game has also been categorized as practical when viewed from the aspects of ease of use, attractiveness, challenge, and its applicability in mathematics learning